Pemberdayaan Ibu Rumah Tangga dalam Upaya Peningkatan Kesejahteraan Keluarga dengan Memanfaatkan Limbah Pohon Pisang - Asah Wiari Sidiq; Asih Niati; Citra Rizkiana; Soedarmadi Soedarmadi (Universitas Muhammadiyah Semarang, 2020)
The potential of banana trees in the Bukit Kencana housing area of Meteseh Village is very high but the surrounding community only uses banana trees limited to fruit and leaves, while the waste is only left to rot. The problem that arises is the unpleasant odor of decay is very disturbing to the community. Though banana tree waste such as banana stem has very high nutritional and fiber content and it can be used for consumption. The objective of Community Service is to provide additional knowledge and creative ideas to open an entrepreneurial mindset so that it can improve the quality of human resources for PKK members in Bukit Kencana Jaya Housing. The method of implementing activities are by giving counseling or lectures, practicing for processing chips, discussions and questions and answers, which begins with providing knowledge about entrepreneurship in looking for business opportunities with natural potential that are available around the Bukit Kencana Jaya housing environment. By organizing the community service activities, it can increase entrepreneurial knowledge and increase insight into how to use and process banana stem into food that can be consumed or sold to other communities so that it will increase income while increasing family welfare.